Implementasi Sistem Informasi Administrasi Desa untuk Meningkatkan Transparansi dan Akuntabilitas Pemerintahan Kelurahan Way Urang Lampung Selatan - Apriyanto, Sigit; Wijaya, Acum; Rozi, Fakhrur; Nurmansyah, Nurmansyah (CV. Tripe Konsultan, 2023)
This community service activity aims to implement a village/sub-district administration information system to improve transparency and accountability in the governance of Way Urang Sub-District, South Lampung Regency. The background of this program is the low effectiveness of administrative services caused by manual record-keeping, limited human resources, and the lack of information technology utilization. The implementation method involved field observation, interviews, focus group discussions (FGD), system design, device installation, training for village officials, service simulations, as well as monitoring and evaluation. The developed information system focused on population data management, issuance of administrative certificates, and financial record-keeping of the sub-district. The results show that village officials were able to adapt to the digital system after receiving mentoring. Administrative services became faster, data were more organized, and financial reports were documented more transparently. Public response was also positive, indicated by increased satisfaction with public services and greater trust in the sub-district government. This activity concludes that the implementation of an administrative information system can strengthen the principles of good governance by enhancing transparency, accountability, and service efficiency. Similar implementations have the potential to be replicated in other sub-districts with adjustments to local needs and regional policy support.